2019
DOI: 10.3389/fmicb.2019.00111
|View full text |Cite
|
Sign up to set email alerts
|

Haitian Variant Vibrio cholerae O1 Strains Manifest Higher Virulence in Animal Models

Abstract: Vibrio cholerae causes fatal diarrheal disease cholera in humans due to consumption of contaminated water and food. To instigate the disease, the bacterium must evade the host intestinal innate immune system; penetrate the mucus layer of the small intestine, adhere and multiply on the surface of microvilli and produce toxin(s) through the action of virulence associated genes. V. cholerae O1 that has caused a major cholera outbreak in Haiti contained several unique genetic signatures. These novel traits are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Increased pathogenic potential was directly demonstrated as the hypervirulent strain outcompeted other strains in cocolonization studies. Furthermore, one of the recent reports from our group has also shown that Haitian variant strains of Vibrio cholerae O1 displayed higher virulence in animal models [17]. However, it was not previously known whether the H20N change in ctxB7 may have contributed to hypertoxigenic phenotype of the Haiti variant isolates.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Increased pathogenic potential was directly demonstrated as the hypervirulent strain outcompeted other strains in cocolonization studies. Furthermore, one of the recent reports from our group has also shown that Haitian variant strains of Vibrio cholerae O1 displayed higher virulence in animal models [17]. However, it was not previously known whether the H20N change in ctxB7 may have contributed to hypertoxigenic phenotype of the Haiti variant isolates.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, Haitian outbreak strain had also been found to exhibit characteristics of hypervirulence with increased pathogenic potential [4]. Recently, one of the reports from our group has shown that Haitian variant strains of Vibrio cholerae O1 manifested markedly higher fluid accumulation and increased mucosal damage in animal models [17]. However, it was not previously known whether the ctxB7 allele may have contributed to hypertoxigenic phenotype of these atypical variants isolates.…”
Section: Introductionmentioning
confidence: 99%
“…IB5230 is considered a hypervirulent strain due to its elevated CT production and colonization of the intestine (Satchell et al, 2016;Ghosh et al, 2019). The CT that was produced by this strain is ctxB7, which differs from the classical type ctxB (ctxB1) at amino acid residue 20.…”
Section: Ib5230 and Derivatives Of Ib5230 That Contain The Toxt-139f mentioning
confidence: 99%
“…This is in line with studies from other regions, such as a study from Kolkata, India, which reports strains possessing Haitianlike traits across 12 states. Evolution of the variant El Tors has offered heightened virulence and toxigenicity as they produce classical cholera toxin that produces more severe disease [39][40][41]. The emergence of polymyxin B susceptibility, one of the traits of classical biotype in recent years, suggest that El Tor biotype strains have morphed into the classical biotype [8].…”
Section: Haitian-like Virulence Genesmentioning
confidence: 99%